Nilai Pancasila Dalam Jejaring Folklore Pela Di Maluku - Salakory, Revaldo Pravasta Julian MB (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2022)
This article examines how local genius within communities has given rise to tangible societal idioms. The purpose of this article is to demonstrate that the values implied in Pancasila serve as a social capital for the Indonesian state. Pancasila, as the foundational ideology of the state, faces challenges due to ideological conflicts and acts of terrorism that threaten the unity of the nation. In the context of Maluku, the values of Pancasila have inherently existed within the bonds of Pela. Since the time of their ancestors, the people of Maluku have upheld a philosophy of brotherhood, even before the emergence of Pancasila democracy. For instance, the author’s research findings related to the harmonious brotherhood between Muslims and Christians are evident in the relationships between the four Pela villages: Haya (Islam), Tehua (Islam), Hatu (Christian), and Wassu (Christian). The values of Pela, upheld by the people of Maluku, extend beyond religious diversity; they are manifested in everyday interactions, where these four villages support each other in economic, political, and social matters. A qualitative case study approach was used to explore the Pela culture of the Maluku people, which embodies the values of Pancasila. Data was collected through direct observation, with the research conducted in the villages of Haya, Hatu, Tehua, and Wassu. Interviews were conducted with local government officials and community members. In addition to field data, the author sought secondary data through literature, including books and scientific journals. This study reveals that the Pela relationship embodies the integrative values inherent in Pancasila.